Christmas Cute Baby Books - Arma, Tom; Arma, Tom; Dreamland Publications (New Delhi Dreamland Publications, 2003)
A delightful book showcasing adorable babies dressed in charming Christmas costumes, captured through the lens of renowned photographer Tom Arma. This book aims to entertain and educate young readers about Christmas traditions.
Book suitable for toddlers. Features vibrant colour photographs of babies dressed in various Christmas-themed costumes. Designed to introduce young children to Christmas traditions in an engaging manner.
Keywords: Christmas, Picture books for children